Cognitive Function and Absence Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the University of Rome, Italy studied executive function and attention in 15 children with childhood absence epilepsy (CAE) (8 boys, 7 girls), under treatment with valproic acid, compared to healthy controls.